The image of the city - Lynch, Kevin, ....- (Cambridge : The MIT Press, 2023)
What does the city's form actually mean to the people who live there? What can the city planner do to make the city's image more vivid and memorable to the city dweller? To answer these questions, Mr. Lynch, supported by studies of Los Angeles, Boston, and Jersey City, formulates a new criterion--imageability--and shows its potential value as a guide for the building and rebuilding of cities. The wide scope of this study leads to an original and vital method for the evaluation of city form. The architect, the planner, and certainly the city dweller will all want to read this book.
Keywords: Landschapsarchitectuur; Stadsontwikkeling; Stedenbouw; Urbanism